Pemberian Terapi Spiritual Emotional Freedom Technique (SEFT) bagi Pasien Terkonfirmasi Covid-19: Provision of Spiritual Emotional Freedom Technique (SEFT) Therapy for Covid-19 Convirmed Patients - Nirva Rantesigi; Agusrianto Agusrianto; Supriadi Supriadi; Ulfa Sufyaningsih (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The covid-19 pandemic can have an impact on both physical and psychological problems for every individual, especially those who have to experience isolation/ quarantine. The forms of distress that arise due to COVID-19 inclide: sleep problems, fear of viruses, difficulty focusing, anxiety, and depression. Spiritual Emotional Freedom Technique (SEFT) is one technique that has been proven effective in dealing with anxiety and increasing motivation. The purpose of this activity is to increase knowledge, reduce anxiety, and reduce stress for confirmed Covid-19 patients. This community service was carried out in the Gebang Rejo Village by using video as a medium.This education related of the impact or danger of anxiety was attended by 24 participants, consisting of 20 women and 4 men. The community was very enthustiastic in listening to the educational materials. After providing education, then continued with the provision of SEFT therapy. From the results of the evaluation of the level of anxiety after community service, it was found that there was a decrease in the number of severe anxiety from 20,8% to 2,4%, moderate anxiety from 37,5% to 20,8% and an increase in mild anxiety from 41,6% to 75%. The conclusion is that giving SEFT therapy can reduce anxiety levels inconvirmed covid-19 patients.